Spontaneous rupture of the liver in a patient admitted for subarachnoid hemorrhage. (2015) - Zatelli, Marianna; Comai, Alessio
Highlights: Spontaneous rupture of the liver is a rare event often associated with the presence of malignant liver disease or occurring in the context of a HELLP syndrome. The treatment of hemorrhage due to spontaneous rupture of the liver includes, in addition to serial monitoring of hemoglobin values, in cases of unstable patients, embolization, hepatic resection and packing. Abstract: INTRODUCTION: Spontaneous rupture of the liver is a rare event often associated with the presence of malignant liver disease or occurring in the context of a HELLP syndrome. We present a case of spontaneous rupture of the liver in a patient admitted to our Intensive Care Department with hemoperitoneum in the aftermath of recent surgical clipping of a cerebral aneurysm. PRESENTATION OF CASE: We report a 50-year-old woman who was transferred from the Bolzano Hospital Department of Neurosurgery to the Intensive Care Unit with anemia and the occurrence of major abdominal pain. DISCUSSION: Spontaneous hepatic rupture remains a rare event, associated more often than not with pregnancy or traumatic events. The treatment of hemorrhage due to spontaneous rupture of the liver includes, in addition to serial monitoring of hemoglobin values, in cases of unstable patients, embolization, hepatic resection and packing. CONCLUSION: The case described here shows that spontaneous rupture of the liver may be due to indefinable causes and that its treatment remains complex and multidisciplinary.